2017
DOI: 10.6002/ect.2016.0156
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Transplant renal artery stenosis is a frequently recognized complication of kidney transplant procedures. A single-center retrospective study was conducted to examine the use of 3-dimensional computed tomography reconstruction in diagnosing transplant artery stenosis. Materials and Methods: During 2013 at our center, 86 patients underwent kidney transplant. All patients underwent ultrasonographic analyses. Patients with clinically suspected transplant renal artery stenosis were examined by 3-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Only 35 studies provided enough data for meta-analysis. An overall summary of the included studies, size, and evidence grading can be found in Supplemental Table S1 2,4,7,12,27-77 . We propose a diagnostic and therapeutic algorithm that reflects the findings, which is displayed in Figure 2 on the basis of the frequency of reporting cutoff parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Only 35 studies provided enough data for meta-analysis. An overall summary of the included studies, size, and evidence grading can be found in Supplemental Table S1 2,4,7,12,27-77 . We propose a diagnostic and therapeutic algorithm that reflects the findings, which is displayed in Figure 2 on the basis of the frequency of reporting cutoff parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Computed tomographic angiography (CTA) has a high spatial resolution, and its three-dimensional post-processing function can directly display the stenosis site and enables evaluation of the degree of stenosis and the condition of adjacent tissues from multiple angles. Moreover, with the use of non-ionic contrast agents, CTA damage to renal function is also significantly reduced [ 7 ]. Magnetic resonance angiography (MRA) is often used in patients with severe renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It has high sensitivity and specificity, and the contrast agent is not toxic to the kidney [ 8 ]. However, it has been shown that MRA tends to overestimate the extent of stenosis [ 7 ]. Digital subtraction angiography (DSA) is still considered the gold standard for TRAS diagnosis and can be used for endovascular treatment [ 2 ].…”
Section: Discussionmentioning
confidence: 99%